The Animation Industry in Jordan : Issues, Challenges, Historical Influences and Recommendations for Development - Manal Hasan, Jamil Barqawi (2019)
The purpose of this research is to provide a clear description of the history and the development of animation scene in Jordan. The research aims to improve and get the better practices of animation industry to become along with the significant approaches in the development and growth of the sector in the country. It introduces the emergence and the history and the current situation of animation industry. It focuses on issues and challenges facing the sector. The research uses the qualitative research approach which was chosen as the most effective and appropriate approach to explore the situation of this industry. Methodology includes several methods such as historical enquiries, interviews, observations, and case studies. The collected data was analyzed using thematic analysis. The research has identified and addressed the challenges and issues that tackle the animation sector. It also reveals the importance of the internet and social media networks for the development of animation sector as a free platform for broadcasting and publishing the creative production of the artists. Internet and social media platforms such as YouTube also work as new medium to archive the animation shorts and clips. The findings and recommendations of this research will result in original knowledge to Jordanian animation makers and for the development of animation industry.